Serology assays to manage COVID-19 - Krammer, Florian; Simon, Viviana (Science (American Association for the Advancement of Science), 2020)
Measurement of antibodies to SARS-CoV-2 will improve disease management if used correctly In late 2019, China reported a cluster of atypical pneumonia cases of unknown etiology in Wuhan. The causative agent was identified as a new betacoronavirus, called severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2), that causes coronavirus disease 2019 (COVID-19) ( 1 ). The virus rapidly spread across the globe and caused a pandemic. Sequencing of the viral genome allowed for the development of nucleic acid–based tests that have since been widely used for the diagnosis of acute (current) SARS-CoV-2 infections ( 2 ). Development of serological assays, which measure the antibody responses induced by SARS-CoV-2 infection (past but not current infections), took longer. This is in part due to bottlenecks with availability of positive control sera and the need for extensive specificity and sensitivity testing in the context of preexisting immunity to seasonal coronaviruses. Serological assays are important for understanding the prevalence of and immunity to SARS-CoV-2.